PENGARUH MEDIA SOSIAL INSTAGRAM TERHADAP PERILAKU KONSUMTIF MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU - Clara Natasya Ketaren; Rr. Sri Kartikowati; Hardisem Syahbrus (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The purpose of this study was to determine the influence of social media Instagram on the consumptive behavior of Economic Education students at the University of Riau. Respondents in this study were students of Economic Education who were in the 2017 2018 and 2019 batches, totaling 70 people. Data collection techniques were carried out using a questionnaire to obtain data on the use of Instagram social media and consumptive behavior. The data collected was then tabulated and analyzed using SPSS version 25. The results showed that social media Instagram had a positive and significant influence on the consumptive behavior of economic education students at the University of Riau. Based on these results, it can be seen that the more time spent using Instagram social media, the higher the tendency of students to behave consumptively.Key word : Instagram Social Media, Consumptive Behavior.